Disaster Safe Education Unit Program As An Effort To Reduce Disaster Risk In School - Wulandari, Dwi; Bangun, Ernalem; Suwarno, Panji; Widodo, Pujo; Kusuma, Kusuma (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Various sectors experienced losses as a result of the disaster. Education is one sector that is badly affected by disasters, especially when disasters occur during school hours. Students, who are the country's future assets, are the biggest victims. In addition, accidents can cause damage to the learning process, school documents, and school facilities. For this reason, disaster risk reduction management must be in place. One way to do this is by providing education about disaster risk reduction. This research uses a qualitative approach, which means describing and explaining what schools are doing to reduce disaster risk by implementing a disaster-safe education unit program. Steps to describe and explain data by referring to expert opinions. This study shows that the Disaster Safe Education Unit (SPAB) program is very important to implement in schools because it can increase the school community's understanding of matters related to disasters. It is hoped that the implementation of the SPAB program will enable schools to remain safe and comfortable and increase students' understanding of how to deal with disasters